KEBERADAAN TOKO TRADISIONAL DAN TOKO MODERN; ASPIRASI PEDAGANG KECIL DAN REGULASI PEMERINTAH KABUPATEN TANAH LAUT - Nurani, Muhammad Fahmi; Ali, Abdul Muta (Jurnal Riset Akuntansi Politala, 2024)
As modern stores dominate and traditional shops cannot compete, various threats emerge, including the loss of traditional shops owing to changing consumer behaviors. The existence of modern shops today creates a dilemma for the government, including in the Tanah Laut Regency area. On the one hand, it creates job opportunities, but on the other, it has the potential to paralyze established traditional shop businesses. It requires the participation of the state, which has the authority to issue regulations. This is a descriptive field research using qualitative methods, with a focus on the sustainability of traditional stores following the existence of modern shops, the aspirations of small traders, and Tanah Laut district government regulations. This research, conducted in 2023, Traditional shop owners experience the influence of modern stores both before and after they open, particularly in terms of income. Because modern stores are more organized and tidier, and rooms are air-conditioned, consumer preferences have shifted. Their aspirations are to progress together, and the site or development zone for modern shops is not close to traditional shops, despite the fact that some are already barely 50 meters away. The sustainability of modern shops today has a significant impact on the sustainability of traditional shops in Tanah Laut Regency. This involves shop development zoning arrangements, collaboration between modern and traditional stores, government assistance in the construction of traditional shops to balance the development of modern shops.